PENGARUH BERMAIN COMPACT DISC INTERAKTIF EDUKATIF TERHADAP PERKEMBANGAN KOGNITIF ANAK USIA 4-5 TAHUN - Renny Safitri; Isti Rusdiyani; Fadlullah (STKIP Subang, 2023)
This study aims to determine whether there is any effect of playing using Educative Interactive Compact Discs on the cognitive development of children aged 4-5 years at RA Nurul Iman Balaraja Kab. Tangerang-Banten. The research method used is pure experiment, with a research design that uses a post-test only control group design. The samples studied at RA Nurul Iman Balaraja, Tangerang-Banten Regency were students in TK A1 class as an experimental class, totaling 15 students and TK A2 as a control class, totaling 15 students using the conventional model. The analysis technique of this research is the results of the analysis using the t-test two averages of the experimental group and the control group obtained the average value of the experimental group ( ) = 41; the average value of the control group kontrol ( ) = 37,2 ; thitung = (7,364) and ttabel = 1,70 at a significant level α = 0,05 with degrees of freedom (dk) = 28. From the result of these calculations the price is obtained thitung (7,364) > ttabel (1,70).based on result of this study, it can be concluded that playing educational interactive compact discs has a significant positive effect in the cognitive development of children aged 4-5 years.